Responsibilities of Business Actors in Forex Investment: A Perspective on Civil Law Protection - Hastia, Hastia; Beddu, Sumiyati; Insani , Nur (Jurnal Litigasi Amsir, 2025)
This study examines the responsibilities of forex investment business actors in Gorontalo to consumers based on KUHPerdata and Undang-Undang Perlindungan Konsumen, by focusing on obstacles in compensating consumers who have suffered losses. Using qualitative methods through interviews and secondary data, the study revealed several important findings. Business actors failed to provide compensation due to the absence of a written agreement, while the confiscation of assets by the authorities has not resulted in prompt compensation for consumers. In addition, the lack of transparency in asset management and the difficulty of consumers in proving claims without a formal contract are major problems. Based on these findings, this study recommends increasing transparency in the asset liquidation process, educating on the importance of written agreements, and encouraging the formalization of the accords to protect consumer rights.